2015
DOI: 10.1007/s11250-015-0975-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of bovine coronavirus in a diarrhea outbreak in pasture-feeding Nellore steers in southern Brazil

Abstract: Worldwide diarrhea outbreaks in cattle herds are more frequently detected in calves being that diarrhea outbreaks in adult cattle are not common. Winter dysentery (WD) is a bovine coronavirus (BCoV) enteric infection that is more reported in Northern hemisphere. Seasonal outbreaks of WD in adult cattle occur mainly in dairy cows. WD has not been described in beef cattle herds of tropical countries. This study describes the molecular detection of BCoV in a diarrhea outbreak in beef cattle steers (Nellore) raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Nearly half of the cattle in our study (46.5%) were infected with BCoV. Previous studies conducted at Brazilian dairy and beef farms have reported BCoV infection frequencies ranging from 15.6-68.6% [4,12,[15][16][17][18][19][20]. These studies predominantly focused on medium and large farms with good nutritional and health management that were located in states considered as large producers of bovine meat and milk for export.…”
Section: Discussionmentioning
confidence: 81%
“…Nearly half of the cattle in our study (46.5%) were infected with BCoV. Previous studies conducted at Brazilian dairy and beef farms have reported BCoV infection frequencies ranging from 15.6-68.6% [4,12,[15][16][17][18][19][20]. These studies predominantly focused on medium and large farms with good nutritional and health management that were located in states considered as large producers of bovine meat and milk for export.…”
Section: Discussionmentioning
confidence: 81%
“…BCoVs are widespread all over the world (Boileau and Kapil 2010 ; Toftaker et al 2017 ). Winter dysentery was typically reported in colder regions but new reports have documented episodes in warmer seasons (summer in Korea) or in tropical countries like Thailand, Brazil and Cuba (Barrera Valle et al 2006 ; Park et al 2006 ; Takiuchi et al 2009 ; Ribeiro et al 2016 ; Singasa et al 2017 ). They can be divided into two groups based on clinical signs.…”
Section: Epidemiologymentioning
confidence: 99%
“…Since the first description of a Brazilian BCoV associated with calf diarrhea, most Brazilian strains of enteric origin have now been described and characterized by molecular methods (Jerez et al, 2005;Takiuchi et al, 2008;Stipp et al, 2009;Ribeiro et al, 2016); in addition, assessment of major public databases did not reveal any description of BRCoV in other South American countries. This study investigates the recent molecular evolution of BCoV by addressing the phylogenetic relationship between the enteric and winter dysentery strains based on a polymorphic region of the Brazilian BRCoV.…”
Section: Introductionmentioning
confidence: 99%